2021
DOI: 10.1038/s41598-021-94594-7
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation products of Danshen relieved dextran sulfate sodium-induced experimental ulcerative colitis in mice

Abstract: With the increased incidence and recognition, ulcerative colitis (UC) has become a global public health problem in the world. Although many immunosuppressant and biological drugs have been used for UC treatment, the cure rate is still very low. It is necessary to find some safe and long-term used medicine for UC cure. Recently, the Chinese traditional herb Danshen has been investigated in the treatment of UC. However, it is a limitation of Danshen that many of the active components in Danshen are not easily ab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 64 publications
(59 reference statements)
0
16
0
1
Order By: Relevance
“…Many active ingredients in TCM are macromolecular substances with limited oral bioavailability, which are difficult to be absorbed by the body. However, probiotics help to further decompose the huge molecules of TCM ( Su et al, 2021 ). After fermentation by Lactobacillus rhamnosus and Bacillus natto, fermented dān shēn can promote proliferation and differentiation of intestinal epithelial cells and regulate immunity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many active ingredients in TCM are macromolecular substances with limited oral bioavailability, which are difficult to be absorbed by the body. However, probiotics help to further decompose the huge molecules of TCM ( Su et al, 2021 ). After fermentation by Lactobacillus rhamnosus and Bacillus natto, fermented dān shēn can promote proliferation and differentiation of intestinal epithelial cells and regulate immunity.…”
Section: Resultsmentioning
confidence: 99%
“…The alleviative effect of fermented dān shēn on DSS-induced colitis is better than that of unfermented dān shēn . In addition, the fermentation process facilitated the decomposition of macromolecular substances in dān shēn which was difficult to be absorbed by the body ( Su et al, 2021 ). At the same time, another study found that probiotic fermented the dried rhizome of Atractylodes macrocephala Koidz.…”
Section: Resultsmentioning
confidence: 99%
“…The contents of tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6) and interleukin-1 beta (IL-1β) in full colons were measured using the bicinchoninic acid (BCA, P0010S) protein assay kit (Beyotime Biotechnology, China) and Enzyme-Linked Immunosorbent Assay (ELISA) kits (Dakowei Biotechnology, Beijing, China) according to our previous method 61 .…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative real-time polymerase chain reaction (RT-qPCR) was performed with 2X Universal SYBR Green Fast qPCR Mix (ABclonal RK21203, China) according to the protocol of the manufacturer. The relative gene expression level of the target genes was calculated by (IL-6) and interleukin-1 beta (IL-1β) in full colons were measured using the bicinchoninic acid (BCA, P0010S) protein assay kit (Beyotime Biotechnology, China) and Enzyme-Linked Immunosorbent Assay (ELISA) kits (Dakowei Biotechnology, Beijing, China) according to our previous method 61 .…”
Section: Rna Extraction and Quantification Of Gene Expressionmentioning
confidence: 99%
“…A considerable amount of research has been performed to explore the interactions between intestinal microbiota (always from healthy volunteers) and the ingredients of certain TCM herbs ( 15 , 16 ). However, few studies have explored the precise interactions of intestinal microbiota derived from particular patients and relevant TCM formulas ( 17 , 18 ). Originally from long-term successful clinical practice, TCM formulas consisting of several herbs create a much more complicated mechanism because different active ingredients can work together to produce a more desired health effect or can cancel out the negative effects associated with a single herb, thereby minimizing side effects and retaining only the desired effect.…”
Section: Introductionmentioning
confidence: 99%